A method that reveals the multi-level ultrametric tree hidden in p -spin-glass-like systems. (10th December 2015) - Baviera, R; Virasoro, M A
Abstract: In the study of disordered models like spin glasses the key object of interest is the rugged energy hypersurface defined in configuration space. The statistical mechanics calculation of the Gibbs–Boltzmann partition function gives the information necessary to understand the equilibrium behavior of the system as a function of the temperature but is not enough if we are interested in the more general aspects of the hypersurface: it does not give us, for instance, the different degrees of ruggedness at different scales. In the context of the replica symmetry breaking (RSB) approach we discuss here a rather simple extension that can provide a much more detailed picture. The attractiveness of the method relies on the fact that it is conceptually transparent and the additional calculations are rather straightforward. We think that this approach reveals an ultrametric organisation with many levels in models like p -spin glasses when we include saddle points. In this first paper we present detailed calculations for the spherical p -spin glass model where we discover that the corresponding decreasing Parisi function q ( x ) codes this hidden ultrametric organisation.